Immunocytoprotection after reperfusion with Kv1.3 inhibitors has an extended treatment window for ischemic stroke - Lee, Ruth D.; Chen, Yi-Je; Singh, Latika; Nguyen, Hai M.; Wulff, Heike (Frontiers in Pharmacology, 2023)
Mechanical thrombectomy has improved treatment options and outcomes for acute ischemic stroke with large artery occlusion. However, as the time window of endovascular thrombectomy is extended there is an increasing need to develop immunocytoprotective therapies that can reduce inflammation in the penumbra and prevent reperfusion injury. We previously demonstrated, that by reducing neuroinflammation, Kv1.3 inhibitors can improve outcomes not only in young male rodents but also in female and aged animals. To further explore the therapeutic potential of Kv1.3 inhibitors for stroke therapy, we here directly compared a peptidic and a small molecule Kv1.3 blocker and asked whether Kv1.3 inhibition would still be beneficial when started at 72 hours after reperfusion. Transient middle cerebral artery occlusion (tMCAO, 90-min) was induced in male Wistar rats and neurological deficit assessed daily. On day-8 infarction was determined by T2-weighted MRI and inflammatory marker expression in the brain by quantitative PCR. In a direct comparison with administration started at 2 hours after reperfusion, the small molecule PAP-1 significantly improved outcomes on day-8, while the peptide ShK-223 failed to reduce infarction and neurological deficits despite reducing inflammatory marker expression. PAP-1 still provided benefits when started 72 hours after reperfusion. Potential interactions with tissue plasminogen activator (tPA) were evaluated in-vitro with a chromogenic assay which showed that PAP-1 does not reduce its proteolytic activity. Our studies suggest that Kv1.3 inhibition for immunocytoprotection after ischemic stroke has a wide therapeutic window and requires brain-penetrant small molecules.